The concept of legal system - Raz, J (1967)
Introduction - The theory of legal system is primarily the study of four problems (1) The problem of existence - what are the criteria for the existence of a legal system? (2) The problems of identity and membership - what are the criteria determining which laws belong be a given system? (3) The problem of structure — Is there of necessity a common internal structure to all legal systems? An internal structure is a structure at internal relations. An internal relation exists between laws if and only if one at them affects the existence or meaning of the other. (4) The problem of content - is there of necessity a common content to all legal systems?